2017
DOI: 10.1080/00380768.2016.1255127
|View full text |Cite
|
Sign up to set email alerts
|

Influence of agricultural activity on soil morphological and physicochemical properties on sandy beach ridges along the east coast of Peninsular Malaysia

Abstract: Along the east coast of Peninsular Malaysia, beach ridges are formed with interspersed swales, which are referred to locally as beach ridges interspersed with swales (BRIS). Although BRIS soils are regarded as problematic lowland soils for agriculture because of their very sandy texture and concomitant infertility, agricultural activities in such soils have been recently increasing. This study was conducted to characterize the BRIS soils and to evaluate the influence of agricultural activities on soil characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…The topography in the village is relatively flat, and leveling for housing had been seldom conducted. The flat topography seems to be common for the BRIS in this district (Khairul et al 2017).…”
Section: Study Areamentioning
confidence: 70%
See 4 more Smart Citations
“…The topography in the village is relatively flat, and leveling for housing had been seldom conducted. The flat topography seems to be common for the BRIS in this district (Khairul et al 2017).…”
Section: Study Areamentioning
confidence: 70%
“…On the other hand, on the BRIS on the east coast of the Malay Peninsula where substantial settlement is believed to have started since the eighteenth or nineteenth century, the soils used for homegardens have not yet been investigated. During the survey in our previous study (Khairul et al 2017), we found that homegarden soils were dark in color down to the deep layers, suggesting a preferable soil condition for plant growth. This finding may provide a clue to help develop sustainable and ecofriendly systems for agriculture in BRIS soils.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations